Emergence of an ST1326 (CG258) Multi-Drug Resistant Klebsiella pneumoniae Co-harboring mcr-8.2, ESBL Genes, and the Resistance-Nodulation-Division Efflux Pump Gene Cluster tmexCD1-toprJ1 in China - Liu, Congcong; Wu, Yuchen; Fang, Yinfei; Sang, Zi; Huang, Ling; Dong, Ning; Zeng, Yu; Lu, Jiayue; Zhang, Rong; Chen, Gongxiang (Frontiers in Microbiology, 2022)
Abstract CG258 is the dominant carbapenemase-producing Klebsiella pneumoniae clone worldwide and treatment of infections caused by this clone relies largely on the last-line antibiotics, colistin and tigecycline. However, the emergence and global dissemination of mcr and tmexCD1-toprJ1 genes have significantly compromised their clinical applications. CG258 K. pneumoniae carrying both mcr and tmexCD1-toprJ1 have not been reported. A colistin-resistant strain T698-1 belonging to ST1326, a member of CG258, was isolated from the intestinal sample of a patient and characterized by the antimicrobial susceptibility testing, conjugation assay, WGS and bioinformatics analysis. It was resistant to colistin, tetracycline, aminoglycoside, fluoroqinolone, phenicols, sulfonamide, and some β-lactams, and positive for mcr-8.2, tmexCD1-toprJ1, and ESBL genes (blaDHA-1 and blaCTX-M-15). The tmexCD1-toprJ1 gene cluster was located in an MDR region flanked by TnAs1 elements on an IncHI1B/FIB plasmid. The genetic context of tmexCD1-toprJ1 was slightly distinct from previously reported Tn5393-like structures, with an IS26 element disrupting the upstream Tn5393 and its adjacent genetic elements. The mcr-8.2 gene was inserted into the backbone of an IncFII/FIA plasmid with the genetic context of ISEcl1-mcr-8.2-orf-ISKpn26. To our knowledge, this is the first report of co-occurrence of mcr-8.2 and tmexCD1-toprJ1 in a CG258 K. pneumoniae strain. Though this strain is tigecycline sensitive, the acquisition of colistin and tigecycline resistance determinants by the endemic CG258 K. pneumoniae clone still poses a serious public health concern. CG258, which became resistant to multiple last resort antibiotics, would be the next emerging superbug.